Simulation-based performance evaluation of kinetic Mashrabiya for thermal comfort and energy efficiency in arid climates: A case study in Biskra, Algeria - Ben Bacha, Cherif; Bourbia , Fatiha (Budownictwo i Architektura / Civil and Architectural Engineering, 2025)
In the hot, dry climate regions of Algeria, traditional buildings are constructed with cooling strategies to cope with harsh climatic conditions. The dominance of direct solar irradiance in these regions requires that building facades be well shaded, allowing for controlled solar transmittance to reduce cooling loads and minimise energy consumption. The Mashrabiya was one of the traditional shading strategies, controlling excess solar radiation and improving interior thermal comfort. Numerous studies have demonstrated that static shading can allow direct radiation to penetrate the building during overheated periods. Shading design must prevent this; however, during colder periods of the year, it is preferable to allow solar radiation to enter the building. This response can be achieved through dynamic shading systems with automated control. This research aims to evaluate the effect and performance of adaptive Mashrabiya as a kinetic sunscreen through parametric simulation, to improve indoor thermal comfort and energy efficiency. These objectives are achieved by integrating solar control with parametric Mashrabiya design to regulate solar radiation intensity and minimise cooling demand. The simulation findings, using parametric tools (Geco and Honeybee plugins for Grasshopper), showed that direct radiation was reduced by 17.9%, resulting in a 43% reduction in energy consumption, accompanied by a corresponding decrease in indoor air temperature of between 4.0°C and 4.8°C. These simulation-based results suggest promising potential for improving building performance and provide valuable insights for early-stage design.